Constructivist Didactics in Teaching Economics: A Shift in Paradigm to be Exemplary Teacher - Woldab, Ziyn Engdasew (JOURNAL OF INDIAN EDUCATION, 2011)
This paper begins with a critique of the prevailing behaviourist instructive which promotes a model of imparting and receiving knowledge in economics education. This approach is criticised for its inadequacy to facilitate higher order thinking, problem solving, creativity and collaborative learning. Contemporarily, research findings in cognitive learning shift the paradigm and provide new dimensions to information processing and constructivist view of teaching economics. It recognises learners as constructor of knowledge and an active participant in the process of learning economic facts and principles, and economics teachers as facilitator of students’ learning. This theoretical paradigm in teaching economics doesn’t disvalue the instructional roles of teachers, rather it advocates that teaching economics should not only instructive but also constructive. Hence, this paper presents the philosophical and psychological roots and major pedagogical principles of constructivism, the rationale for adoption of traditional instructional perspectives with modern constructivist approach and its practical implications in teaching economics.